Instilling Religious Values Through The Tahfidzul Qur’an Program Activities (A Study At Pondok Pesantren Tri Bhakti At-Taqwa Rama Puja, East Lampung Regency) - Agung Nugroho; Akim Musolah; Suwardi Suwardi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Character development in children needs to be nurtured, and once children are entrusted to a school, the responsibility for that development lies in the hands of the teachers. One effective way to address this need is by instilling religious values as a means of shaping the students’ character. However, despite the administrators’ efforts to cultivate students' personalities, observations indicate that some students still exhibit behaviors that are not in line with the expected character of a santri (Islamic boarding school student). This situation is caused by several factors, such as disregarding the dormitory rules, ignoring the guidance provided by the administrators during religious value education, being lazy in reviewing their memorization, and so forth. This study is a field research conducted at Pondok Pesantren Tri Bhakti At-Taqwa Rama Puja in East Lampung Regency, focusing on the instillation of religious values through the Tahfidzul Qur’an program. In collecting the required data, the researcher employed observation, interviews, and documentation techniques. The gathered data were then compiled and analyzed to draw conclusions. Based on the results of the study, it can be concluded that Pondok Pesantren Tri Bhakti At-Taqwa Rama Puja in East Lampung Regency plays a significant role in instilling religious values through the Tahfidzul Qur’an program. The tahfidz program activities are implemented in several stages: (1) students read the verses to be memorized together with the tahfidz teacher, followed by individual memorization recitations; (2) the memorization activities are carried out using the sima’i and jama’i methods, which are considered easy to understand and follow by the students; (3) the program is evaluated by having